Bonded body and ceramic copper circuit board
By forming a stacked structure with a specific Ti concentration distribution in the bonding layer of the ceramic copper circuit substrate, the problem of reducing TCT characteristics caused by uneven Ti distribution is solved, and a more stable high TCT characteristics are achieved.
Patent Information
- Application Number
- CN202411735018.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-27
- Filing Date
- 2021-05-17
- Publication Date
- 2025-03-07
AI Technical Summary
The uneven distribution of Ti in the existing ceramic copper circuit substrates in the bonding layer leads to a decrease in TCT characteristics, especially when the bonding body becomes larger.
By forming a laminated structure with a first region and a second region in the bonding layer, the first region has titanium as the main component, the second region has a high Ti concentration, and the Ti concentration ratio M1/M2 is controlled to be within the range of 0.1 to 5 to uniformize the Ti distribution of the bonding layer.
The uniformization of Ti distribution in the bonding layer is achieved, the TCT characteristics of the ceramic copper circuit substrate are improved, and stability is maintained when the bonding size increases.
Smart Images

Figure CN119581422A_ABST
Abstract
Description
[0001] This application is a divisional application of the application with application number "202180036089.5", application date May 17, 2021, and invention name "Joint body, ceramic copper circuit substrate, and semiconductor device". Technical Field
[0002] The embodiments described below relate to a bonded body, a ceramic copper circuit board, and a semiconductor device. Background Art
[0003] The joint body of a ceramic substrate and a copper plate is used as a circuit substrate for mounting semiconductor elements and the like. International Publication No. 2018 / 021472 (Patent Document 1) discloses a ceramic copper circuit substrate formed by joining a ceramic substrate and a copper plate. In Patent Document 1, a solder containing Ag, Cu, Ti, etc. is used in the joining layer. In addition, the temperature cycle test (TCT) characteristics are improved by controlling the nanoindentation hardness of the joining layer. In Patent Document 1, the nanoindentation hardness is controlled by allowing AgTi crystals and TiC to exist in the joining layer. In Patent Document 1, the joining strength and TCT characteristics are improved by controlling the nanoindentation hardness.
[0004] On the other hand, when the size of the bonded body increases, the TCT characteristics may decrease.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2018 / 021472
[0008] Patent Document 2: Japanese Patent No. 4077888 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The reason for this is that the distribution of Ti in the bonding layer is the cause. A bonded body using Ag-Cu-Ti solder is disclosed in Japanese Patent Gazette No. 4077888 (Patent Document 2). In Patent Document 2, a titanium nitride (TiN) layer is formed in the bonding layer. The titanium nitride layer is a hard layer with a Vickers hardness of about 1100 to 1300. It is known that the difference in hardness between the TiN layer and the AgCu layer is the cause.
[0011] An object of the present invention is to provide a joined body in which the distribution of Ti in the joining layer is controlled in order to cope with such a problem.
[0012] Means used to solve problems
[0013] The joint body of the embodiment comprises: a ceramic substrate, a copper plate, and a joint layer disposed on at least one side of the ceramic substrate and joining the ceramic substrate to the copper plate. The joint layer contains titanium. The joint layer has a first region and a second region located between the first region and the copper plate, the first region includes a layer having titanium as a main component, and the layer is formed at the interface between the joint layer and the ceramic substrate. When the Ti concentration in the range of 200 μm×thickness of the respective measurement regions of the first region and the second region is measured by EDX, the ratio M1 / M2 of the titanium concentration M1at% of the first region of the joint body to the titanium concentration M2at% of the second region is 0.1 to 5. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a diagram showing an example of a joined body according to an embodiment.
[0015] Figure 2 This is a diagram showing an example of a bonding layer of a bonded body according to an embodiment.
[0016] Figure 3 This is a diagram showing an example of a ceramic copper circuit board according to an embodiment.
[0017] Figure 4 Another example of the ceramic copper circuit board according to the embodiment is shown.
[0018] Figure 5 It is a diagram showing an example of a semiconductor device according to an embodiment. DETAILED DESCRIPTION
[0019] The joint body of the embodiment comprises: a ceramic substrate, a copper plate, and a joint layer disposed on at least one side of the ceramic substrate and joining the ceramic substrate to the copper plate. The joint layer contains titanium. The joint layer has a first region and a second region located between the first region and the copper plate, the first region includes a layer having titanium as a main component, and the layer is formed at the interface between the joint layer and the ceramic substrate. When the Ti concentration in the range of 200 μm×thickness of the respective measurement regions of the first region and the second region is measured by EDX, the ratio M1 / M2 of the titanium concentration M1at% of the first region of the joint body to the titanium concentration M2at% of the second region is 0.1 to 5.
[0020] Figure 1 An example of a joined body according to the embodiment is shown. Figure 2 An example of a bonding layer of a bonded body according to an embodiment is shown. Figure 1 and Figure 2 In the figure, 1 is a bonded body, 2 is a ceramic substrate, 3 is a copper plate, 4 is a bonding layer, 5 is a first region, and 6 is a second region.
[0021] Figure 1 The joint body 1 is shown in which two copper plates 3 are arranged on both sides of the ceramic substrate 2 via the bonding layer 4. In the example shown in the figure, the vertical and horizontal dimensions of the ceramic substrate 2 and the two copper plates 3 are the same. The joint body of the embodiment is not limited to such a mode, and may also have a structure in which the copper plate is provided only on one side of the ceramic substrate 2. In addition, the vertical and horizontal dimensions of the ceramic substrate 2 may also be different from the vertical and horizontal dimensions of the copper plate 3.
[0022] The joint body 1 includes a ceramic substrate 2, a copper plate 3, and a joint layer 4. The joint layer 4 is arranged on at least one side of the ceramic substrate and joins the ceramic substrate 2 and the copper plate 3. In addition, the joint layer 4 contains Ti and has a first region 5 and a second region 6. The first region 5 includes a layer with titanium as a main component. The layer with titanium as a main component is formed at the interface between the joint layer 4 and the ceramic substrate 2. The second region 6 is located between the first region 5 and the copper plate.
[0023] Figure 2 The conceptual diagram of the bonding layer 4 is shown. The bonding layer 4 has a stacked structure of a first region 5 and a second region 6 .
[0024] The first region 5 includes a region of a layer having titanium as a main component. A layer having titanium as a main component refers to a region in which titanium is present at 30 at% or more. In addition, a layer having titanium as a main component refers to a layer in which any one or more of titanium simple substance, oxide, nitride, silicide, and oxynitride are present. For example, in the case where titanium silicide is formed on a titanium nitride layer and is in contact with the titanium nitride layer, the layers having titanium as a main component are the titanium silicide and the titanium nitride layer. That is, in the case where the titanium silicide is directly in contact with the titanium nitride layer, the titanium nitride layer and the titanium silicide are counted as the layer having titanium as a main component.
[0025] In addition, the first region 5 exists along the interface between the ceramic substrate 2 and the bonding layer 4. Therefore, a layer containing titanium as a main component is formed along the surface of the ceramic substrate 2.
[0026] The layer containing titanium as the main component is continuously formed in the thickness direction from the ceramic substrate 2. For example, titanium nitride present at a position away from the layer containing titanium as the main component is counted as the second region 6. In the case where titanium simple substance, oxide, and oxynitride are present at a position away from the layer containing titanium as the main component, they are counted as the second region 6.
[0027] Examples of Ti oxides include TiO2 (titanium oxide). Examples of Ti nitrides include TiN (titanium nitride) and Ti2N (titanium nitride). Examples of Ti oxynitrides include TiON (titanium oxynitride). Ti oxides, Ti nitrides and Ti oxynitrides are not limited to the substances listed in the examples. For example, the atomic ratio of titanium to nitrogen in TiN (titanium nitride) is 1:1, which is a stable stoichiometry, but it can also deviate from the stoichiometry. In addition, the layer with titanium as the main component can be a layer in which two or more of the materials listed in the examples are mixed. "Titanium nitride" means a compound of titanium and nitrogen. When recorded as TiN, the atomic ratio of titanium to nitrogen is not limited to 1:1, and it means a compound of titanium and nitrogen.
[0028] In addition, in the case where the ceramic substrate is a nitride-based ceramic substrate, the layer with titanium as the main component contains titanium nitride as the main component. In addition, in the case of a nitride-based ceramic substrate, titanium nitride containing more than 30 at% of titanium constitutes the layer with titanium as the main component. In addition, titanium nitride can exist in one or more selected from cubic crystals, hexagonal crystals, and tetragonal crystals. In addition, in the case of a nitride-based ceramic substrate, the first region 5 can be obtained based on the titanium nitride layer formed on the surface of the ceramic substrate 2. That is, the titanium amount M1 of the first region 5 can be obtained using the maximum thickness of the titanium nitride layer.
[0029] When the bonding layer 4 contains Ag, a layer containing titanium nitride as a main component may contain a material selected from Ti2N, Ti 0.83 N 0.17 and one or more of metal Ti. Ti2N, Ti 0.83 N 0.17 Or metallic Ti becomes a Ti-rich phase with a large amount of Ti. By allowing a Ti-rich phase to exist in a layer with titanium nitride as the main component, the amount of Ti present in the second region 6 can be controlled. In addition, when the bonding layer does not contain Ag, it is preferred that a Ti-rich phase exists in the layer with titanium nitride as the main component in the range of 0at% to 10at%. In addition, 0at% of the Ti-rich phase means below the detection limit. The Ti-rich phase contains more Ti than a region where the atomic ratio of Ti to N is 1:1. By increasing the amount of Ti in the first region 5, the ratio of the titanium concentration in the first region 5 to the titanium concentration in the second region 6 can be controlled.
[0030] In addition, when the ceramic substrate is an oxide-based ceramic, the layer containing titanium as the main component contains titanium oxide as the main component. In addition, titanium oxide includes TiO2, TiO, Ti3O2, etc. Therefore, the layer containing titanium as the main component can be identified based on the titanium oxide layer.
[0031] The layer with titanium as the main component is formed on the surface of the ceramic substrate 2. The layer with titanium as the main component does not need to have a certain thickness in the surface direction. In addition, the layer with titanium as the main component only needs to be present in more than 90% of the interface between the bonding layer 4 and the ceramic substrate 2. The interface of the ceramic substrate 2 refers to the area on the surface of the ceramic substrate 2 where the bonding layer 4 is provided. Even if it is the surface of the ceramic substrate 2, the area where the bonding layer 4 is not provided will not be counted.
[0032] The layer with titanium as the main component can be confirmed by EDX (energy dispersive X-ray) analysis. EDX analysis is performed on any cross section of the joint body 1. In the EDX analysis, regional analysis is performed within the measurement area in the joint layer 4. The measurement area is a range of 200μm in length × thickness. If a layer with titanium as the main component is observed on the surface of the ceramic substrate 2 above 180μm (=200μm×90%) within the measurement area, it can be considered that there is a layer with titanium as the main component.
[0033] In addition, regional analysis is performed by EDX analysis, thereby analyzing the components other than Ti contained in the layer with titanium as the main component. For example, if nitrogen is detected by regional analysis, it is considered that the layer with titanium as the main component contains Ti nitride. In addition, when the boundary between the ceramic substrate 2 and the bonding layer 4 is difficult to distinguish, TEM (transmission electron microscope) analysis is used. A method of performing EDX point analysis on the bonding layer 4 based on the results of TEM analysis to detect Ti and N is effective. Elements other than nitrogen can also be detected by the same method.
[0034] The thickness of the first region 5 is obtained by the width between the closest and farthest parts of the ceramic substrate 2 with the layer containing titanium as the main component in the measurement region. The layer containing titanium as the main component is formed along the surface of the ceramic substrate 2. There are tiny concave and convex surfaces on the surface of the ceramic substrate 2. Therefore, the thickness of the first region 5 is obtained by the above method. The thickness of the first region 5 is obtained by this method, so the first region 5 also includes the region other than the layer containing titanium as the main component.
[0035] In addition, within the measurement area, a line passing through the nearest portion and parallel to the surface direction is used as the boundary line between the ceramic substrate 2 and the first area 5. The surface direction is a direction perpendicular to the thickness direction connecting the ceramic substrate 2 and the bonding layer 4. The boundary line between the ceramic substrate 2 and the first area 5 is called the first boundary line.
[0036] In the measurement area, a line passing through the farthest part and parallel to the plane direction is used as the boundary line between the first area 5 and the second area 6. The boundary line between the first area 5 and the second area 6 is called the second boundary line. Therefore, the thickness of the first area 5 becomes the width between the first boundary line and the second boundary line.
[0037] The thickness of the second region 6 is the width from the second boundary line to the boundary between the bonding layer 4 and the copper plate 3. The boundary between the bonding layer 4 and the copper plate 3 is the farthest part (the part farthest from the ceramic substrate 2) of the part where the components of the bonding layer are connected and connected to the copper plate 3 in the measurement area. From the vicinity of the interface between the second region 6 and the copper plate 3 to the copper plate 3, the detection amount of the components of the bonding layer is sharply reduced, and the components of the bonding layer become discontinuous. In the measurement area, the line that is the farthest part of the part connected to the copper plate 3 by the components of the bonding layer and parallel to the surface direction is called the third boundary line. Therefore, the thickness of the second region 6 becomes the width from the second boundary line to the third boundary line. There is an area in the measurement area where the components constituting the bonding layer 4 are connected to the first region 5. The part where this area is connected to the copper plate 3 is the part where the components of the bonding layer 4 are connected and connected to the copper plate 3.
[0038] For example, the case where the components constituting the bonding layer 4 are Ag (silver), Cu (copper), Sn (tin), and Ti (titanium) is used for explanation. The components of the bonding layer 4 are connected, indicating a state in which a mixed component selected from one or more of Ag, Cu, Sn, and Ti is connected from the first region 5 to the copper plate 3. The mixed component represents a state in which Ag, Cu, Sn, and Ti are mixed as a single component or alloyed. Therefore, even if the components constituting the bonding layer 4 are diffused in the copper plate 3, they are not counted as the third boundary line if they are not connected. Unconnected means that the components of the bonding layer are distributed in a discontinuous state. In addition, when it is impossible to distinguish between the Cu constituting the bonding layer 4 and the Cu of the copper plate 3, the third boundary line is counted by other components.
[0039] When Ti concentrations in the range of 200 μm×thickness of the measurement regions of the first region 5 and the second region 6 were measured by EDX, the ratio M1 / M2 of the Ti concentration M1 at % in the first region 5 and the Ti concentration M2 at % in the second region 6 of the joint body of the embodiment was 0.1-5.
[0040] M1 / M2, which is the ratio of Ti concentration, is 0.1 to 5, indicating that there is a relatively large amount of Ti distributed in the second region 6. The bonding technology using Ti includes the active metal bonding method. The active metal bonding method forms a titanium nitride (TiN) layer as shown in Patent Documents 1 and 2. The titanium nitride layer is equivalent to a layer with titanium as the main component. In the past, Ti was concentrated in the titanium nitride layer, so the Ti concentration in the region equivalent to the second region 6 was low. Therefore, in the past, M1 / M2 was above 20. The titanium nitride layer is a hard layer. It is known that when there is a difference in hardness between the first region and the second region, it will have an adverse effect on the TCT characteristics. In addition, when M1 / M2 is less than 0.1, the amount of Ti in the first region 5 is small. When the amount of Ti in the first region 5 is small, the amount of titanium nitride is insufficient, so there is a possibility of reduced bonding strength. In addition, in Patent Documents 1 and 2, the layer with titanium as the main component contains titanium nitride (TiN). This is because the nitride ceramic substrate reacts with Ti. Therefore, when an oxide ceramic substrate is used, titanium oxide is formed.
[0041] In the active metal bonding method, Ag or Cu is used as the main component, and an active metal brazing material containing Ti as the active metal is used. In addition, Sn (tin) or In (indium) is sometimes added to the active metal brazing material. Among active metal brazing materials, Ti is a relatively hard material. Therefore, by controlling the Ti concentration in the bonding layer, the hardness in the bonding layer can be made more homogenous. Therefore, M1 / M2 is preferably 0.1 to 5, and more preferably 0.5 to 4.
[0042] SEM-EDX is used for EDX analysis. JSM-IT100 manufactured by JEOL or a device with equivalent performance is used in SEM. In addition, EX-9440IT4L11 manufactured by JEOL or a device with equivalent performance is used in EDX. First, regional analysis of the measurement area 200μm×thickness is performed by EDX. The measurement area is set to 200μm×thickness because this area is suitable for investigating the distribution of the components of the bonding layer. When the measurement area is less than 200μm, it is easily affected by the state of diffusion of the material contained in the bonding layer to the copper plate. The particle size of the copper particles contained in the copper plate is about 10 to 1000μm. The grain boundary of the copper plate becomes the diffusion path of the material contained in the bonding layer. In order to suppress the influence of the analysis of the position that is easy to diffuse and the position that is not easy to diffuse, the measurement area is preferably 200μm. When the measurement area is larger than 200μm, the deviation of the Ti concentration cannot be measured. In addition, as described later, in order to measure the deviation of the Ti concentration in the second region, the measurement area is also preferably 200μm. M1 / M2 is calculated by taking the average value of any three locations.
[0043] The deviation of the Ti concentration in the second region 6 is preferably within ±20%. The deviation of the Ti concentration in the second region 6 is the difference between the Ti concentration in the second region 6 in the first measurement region and the Ti concentration in the second region 6 in another measurement region different therefrom. The Ti concentration in the first measurement region is defined as M2a, and the Ti concentration in the other measurement region different therefrom is defined as M2b. The deviation V of the Ti concentration in the second region 6 is calculated by V(%)=[(M2a-M2b) / M2a]×100.
[0044] The TCT characteristics can be improved by suppressing not only the Ti concentration in the first region 5 and the second region 6 but also the variation in Ti concentration in the second region 6. Therefore, the variation in Ti concentration in the second region 6 is preferably within ±20%, more preferably within ±10%.
[0045] The thickness of the first region is preferably 5 μm or less. The first region 5 includes a layer containing titanium as a main component. When the first region 5 is thicker than 5 μm, titanium is excessively concentrated in the first region 5, and M1 / M2 may exceed 5.
[0046] The thickness of the second region is preferably 5 μm to 70 μm. It is preferable to control the Ti concentration of the second region 6 having a predetermined thickness.
[0047] The Ti concentration in the second region is preferably in the range of 0.5at% to 15at%. When the Ti concentration in the second region 6 is less than 0.5at%, there is a possibility that the amount of Ti in the second region 6 is insufficient. When the amount of Ti is small, the deviation of the Ti concentration in the second region 6 tends to become larger. In addition, when the Ti concentration exceeds 15at%, M1 / M2 tends to be less than 0.1. Therefore, the Ti concentration in the second region 6 is preferably 0.5at% to 15at%, and more preferably 1at% to 10at%. When measuring the Ti concentration at% in the second region 6, it is obtained by removing O (oxygen), N (nitrogen), and C (carbon). As described later, metal components such as Ag and Cu exist in the M2 region. In order to control the existence ratio of metal components other than Ti, at% is effective.
[0048] The thickness of the copper plate is preferably 0.6 mm or more. The ceramic substrate is preferably any one selected from a silicon nitride substrate and an aluminum nitride substrate.
[0049] A copper plate or a copper alloy plate can be used as the copper plate 3. The copper plate 3 is preferably formed of oxygen-free copper. Oxygen-free copper has a copper purity of 99.96 wt% or more as specified in JIS-H-3100 (ISO1337, etc.).
[0050] The copper plate 3 is used as a circuit part or a heat sink. By increasing the thickness of the copper plate 3, the current carrying capacity, heat dissipation, etc. can be improved. Therefore, the thickness of the copper plate 3 is preferably 0.6 mm or more, and more preferably 0.8 mm or more.
[0051] As the ceramic substrate 2, a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, an aluminum silicon alloy substrate, etc. can be used. The thickness of the ceramic substrate 2 is preferably 0.1 mm to 1 mm. When the substrate thickness is less than 0.1 mm, there is a concern that the strength may be reduced. In addition, when it is thicker than 1 mm, the ceramic substrate becomes a thermal resistor, and there is a possibility that the heat dissipation of the joint body is reduced.
[0052] The three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more. The thermal conductivity is preferably 80 W / m·K or more. By increasing the strength of the silicon nitride substrate, the thickness of the substrate can be reduced. Therefore, the three-point bending strength of the silicon nitride substrate is preferably 600 MPa or more, and more preferably 700 MPa or more. Thus, the thickness of the silicon nitride substrate is preferably reduced to less than 0.40 mm, and further less than 0.30 mm.
[0053] The three-point bending strength of the aluminum nitride substrate is about 300 to 450 MPa. On the other hand, the thermal conductivity of the aluminum nitride substrate is 160 W / m·K or more. Since the strength of the aluminum nitride substrate is low, the substrate thickness is preferably 0.60 mm or more.
[0054] The three-point bending strength of an alumina substrate is about 300 to 450 MPa, but the price of an alumina substrate is low. In addition, the three-point bending strength of an aluminum silicon alloy substrate is as high as about 550 MPa, but the thermal conductivity is about 30 to 50 W / m·K.
[0055] As the ceramic substrate 2, any one of a silicon nitride substrate and an aluminum nitride substrate is preferred. The silicon nitride substrate and the aluminum nitride substrate are nitride ceramic substrates. Nitride ceramic reacts with an active metal brazing material containing Ti to form titanium nitride. Therefore, it is easy to form a layer with titanium nitride as the main component in the first region 5.
[0056] In addition, the oxide ceramic reacts with the active metal brazing material containing Ti to form titanium oxide. Therefore, it is easy to form a layer containing titanium oxide as a main component in the first region 5. The oxide ceramic is an alumina substrate, an aluminum silicon alloy substrate, or the like.
[0057] It is preferable to arrange|position the copper plate 3 on both surfaces of the ceramic substrate 2. By joining the copper plate to both surfaces, the warping of a joined body can be suppressed.
[0058] The second region preferably contains one or two selected from silver and copper. In addition, the second region preferably contains one or two selected from tin and indium.
[0059] In order to make the second region 6 contain silver or copper, it is effective to make the active metal brazing filler metal contain silver or copper. In order to make the second region 6 contain tin or indium, it is effective to make the active metal brazing filler metal contain tin or indium.
[0060] The active metal brazing filler metal composition preferably contains 0 mass% to 70 mass% of Ag (silver), 15 mass% to 85 mass% of Cu (copper), and 1 mass% to 15 mass% of Ti (titanium) or TiH2 (titanium hydride). In addition, when both Ti and TiH2 are used, their total is set within the range of 1 to 15 mass%. In addition, when both Ag and Cu are used, it is preferred that Ag is 20 to 60 mass% and Cu is 15 to 40 mass%.
[0061] The active metal brazing filler metal may contain 1 to 50% by mass of one or both of Sn (tin) and In (indium), as required. The content of Ti or TiH2 is preferably 1 to 15% by mass. The active metal brazing filler metal may contain 0.1 to 2% by mass of C (carbon), as required.
[0062] The ratio of the active metal brazing filler metal composition is calculated by setting the total of the mixed raw materials to 100 mass %. For example, when the active metal brazing filler metal is composed of three kinds of Ag, Cu, and Ti, it is Ag+Cu+Ti=100 mass %. When the active metal brazing filler metal is composed of four kinds of Ag, Cu, TiH2, and In, it is Ag+Cu+TiH2+In=100 mass %. When the active metal brazing filler metal is composed of five kinds of Ag, Cu, Ti, Sn, and C, it is Ag+Cu+Ti+Sn+C=100 mass %.
[0063] Ag or Cu is a component of the base material of the solder. Sn or In has the effect of lowering the melting point of the solder. C (carbon) has the effect of controlling the fluidity of the solder or reacting with other components to control the structure of the bonding layer. Therefore, as the components of the solder, Ag-Cu-Ti, Ag-Cu-Sn-Ti, Ag-Cu-Ti-C, Ag-Cu-Sn-Ti-C, Ag-Ti, Cu-Ti, Ag-Sn-Ti, Cu-Sn-Ti, Ag-Ti-C, Cu-Ti-C, Ag-Sn-Ti-C, Cu-Sn-Ti-C can be cited. In can be used instead of Sn. Both Sn and In can also be used. Low melting point metals such as Bi (bismuth), Sb (antimony), and Ga (gallium) can be used instead of Sn and In.
[0064] The melting point of the active metal brazing filler metal is preferably 700° C. or less. By lowering the melting point of the brazing filler metal, the bonding temperature can be lowered. By lowering the bonding temperature, the Ti concentration in the first region 5 and the Ti concentration in the second region 6 can be controlled.
[0065] In the DSC curve of the active metal brazing filler metal, the maximum endothermic peak is preferably within a range of 550° C. to 700° C. The temperature at which the maximum endothermic peak appears in the DSC curve is defined as the melting point of the active metal brazing filler metal.
[0066] The DSC curve is obtained by measuring the peaks of endothermic reaction and exothermic reaction using a differential scanning calorimeter (DSC). Negative peaks are endothermic reactions, and positive peaks are exothermic reactions.
[0067] The DSC curve is measured by a temperature curve consisting of a heating process, a holding process at a certain temperature, and a cooling process. Regarding the temperature curve, the heating process is heated from room temperature to 500°C at a heating rate of 5°C / min. Next, the heating process is held at 500°C for 60 minutes. Then, the heating process is heated to 845°C at a heating rate of 5°C / min. In the holding process, it is held at 845°C for 30 minutes. The cooling process is cooled from 845°C to room temperature at a cooling rate of 5°C / min.
[0068] As DSC, a TGA-DSC simultaneous thermal analysis device STA449-F3-Jupiter manufactured by NETZSCH or a device having equivalent performance can be used. In addition, the measurement is performed by dropping an appropriate amount of brazing material into an alumina container and performing the measurement in an Ar (argon) gas flow. The measurement must be performed in an Ar atmosphere to prevent the brazing material from reacting with the atmosphere.
[0069] In the heating process of the DCS curve, the detected temperature of the maximum endothermic peak in the temperature range of 550°C to 800°C is taken as the melting point. The melting point of the brazing material is below 700°C, which means that the maximum endothermic peak is in the range of 550 to 700°C. In addition, even if there is a negative peak at less than 550°C, it may not be counted as an endothermic peak. The endothermic reaction is caused by the melting and decomposition of the active metal brazing material. For example, if titanium hydride (TiH2) is used as the active metal, a negative peak is detected around 500°C. This peak is when TiH2 decomposes into Ti and H.
[0070] The above-mentioned bonded body is suitable for a ceramic copper circuit substrate. A circuit structure is provided to the copper plate disposed on at least one surface of the ceramic substrate. In this way, a ceramic copper circuit substrate using the bonded body of the embodiment is obtained.
[0071] Figure 3 An example of a ceramic copper circuit substrate according to an embodiment is shown. Figure 3 In the figure, 7 is a circuit part. 8 is a heat sink. 10 is a ceramic copper circuit substrate. The circuit part 7 is formed by giving a circuit structure to the copper plate 3 on the front side. In addition, the heat sink 8 is formed by processing the copper plate 3 on the back side. Figure 3In the figure, two circuit parts 7 are provided. The ceramic copper circuit substrate of the embodiment is not limited to the structure shown in the figure. The number, shape, etc. of the circuit parts 7 are arbitrary. In addition, the circuit part 7 can be formed by giving a circuit structure to the copper plates 3 on both sides. The side of the circuit part 7 or the side of the heat sink 8 can be inclined relative to the thickness direction. A bonding layer protruding part where the bonding layer 4 protrudes from the end of the circuit part 7 or the end of the heat sink 8 can be provided. The ceramic copper circuit substrate 10 of the embodiment controls the Ti distribution in the bonding layer 4, and therefore, the TCT characteristics can be improved.
[0072] Figure 4 This is a diagram showing another example of the ceramic copper circuit board according to the embodiment.
[0073] Through holes may be provided in the ceramic substrate, and the copper plate on the front side and the copper plate on the back side may be electrically connected via the through holes. Figure 4 An example of a ceramic copper circuit board having through holes is shown. Figure 4 It is a cross-sectional view of a portion where a through hole is provided. Figure 4 In the figure, 10 is a ceramic copper circuit substrate. 2 is a silicon nitride substrate. 4 is a bonding layer. 7a is a circuit portion on the front side. 7b is a circuit portion on the back side. 9 is a through hole. Figure 4 In the embodiment, the circuit portion 7a and the circuit portion 7b are electrically connected via the through hole 9. Figure 4 In the figure, a plurality of through holes 9 respectively connect a plurality of circuit parts 7a and a plurality of circuit parts 7b together. The embodiment is not limited to such a structure. In the ceramic copper circuit substrate 10, the through hole 9 can be provided only in a part of the plurality of circuit parts 7a. The through hole 9 can also be provided only in a part of the circuit part 7b. It is preferred that the inside of the through hole 9 is filled with the same material as the bonding layer 4. The structure inside the through hole 9 is not particularly limited as long as the circuit part on the front side is connected to the circuit part on the back side. Therefore, a metal film can be provided only on the inner wall of the through hole 9. On the other hand, by filling with the same material as the bonding layer 4, the bonding strength can be improved.
[0074] Figure 5 It is a diagram showing an example of a semiconductor device according to an embodiment.
[0075] The ceramic copper circuit board of the embodiment is suitable for a semiconductor device. In the semiconductor device, a semiconductor element is mounted on a copper plate of the ceramic copper circuit board via a bonding layer. Figure 5 An example of a semiconductor device is shown. Figure 5 In the figure, 10 is a ceramic copper circuit substrate. 7 is a circuit unit. 8 is a heat sink. 20 is a semiconductor device. 21 is a semiconductor element. 22 is a bonding layer. 23 is a wire bonding. 24 is a metal terminal. Figure 5In the embodiment, a semiconductor element 21 is bonded to a circuit portion of a ceramic copper circuit substrate 10 via a bonding layer 22. Similarly, a metal terminal 24 is bonded via the bonding layer 22. Adjacent circuit portions are electrically connected to each other via wire bonding 23. Figure 5 In addition to the semiconductor element 21, a wire bond 23 and a metal terminal 24 are also bonded to the ceramic copper circuit substrate 10. The semiconductor device of the embodiment is not limited to such a structure. For example, only one of the wire bond 23 and the metal terminal 24 may be provided. The semiconductor element 21, the wire bond 23, and the metal terminal 24 may be provided in plurality in the circuit portion on the surface side. The copper plate on the back side may be given a circuit structure, and the semiconductor element 21, the wire bond 23, and the metal terminal 24 may be bonded. The metal terminal 24 may be applied in various shapes such as a lead frame shape and a convex shape.
[0076] By using the bonded body of the embodiment for the above-mentioned ceramic copper circuit board or semiconductor device, the TCT characteristics can be improved.
[0077] Next, a method for producing the bonded body of the embodiment will be described. The bonded body of the embodiment may have the above-mentioned structure, and its production method is not limited. Here, an example of a method for obtaining the bonded body of the embodiment with a good yield will be described.
[0078] First, a ceramic substrate 2 is prepared. The ceramic substrate 2 is a silicon nitride substrate, an aluminum nitride substrate, an aluminum oxide substrate, or an aluminum silicon alloy substrate, etc. The aluminum silicon alloy substrate is a substrate in which aluminum oxide and zirconium oxide are mixed.
[0079] A copper plate or a copper alloy plate can be used as the copper plate 3. In addition, the copper plate 3 is preferably oxygen-free copper. Oxygen-free copper has a copper purity of 99.96 wt % or more as shown in JIS-H-3100.
[0080] Next, an active metal brazing filler metal paste containing Ti is prepared. One or two selected from Ag and Cu may be added to the active metal brazing filler metal containing Ti as components other than Ti. In addition, one or two selected from Sn and In may be added to the active metal brazing filler metal. C (carbon) may be added to the active metal brazing filler metal. In addition, compounds such as TiH2 may be added to the active metal brazing filler metal as Ti. The composition ratio (mass %) of each component is as described above.
[0081] In order to control the melting point of the active metal brazing material, it is effective to control the composition, the particle size of the raw material powder, etc. As mentioned above, Sn or In has the effect of lowering the melting point of the brazing material. It is effective to make the powder particle size of Sn or In the components constituting the brazing material the largest. For example, when using Ag-Cu-Sn-Ti brazing material, the particle size of Sn powder is made the largest among Ag powder, Cu powder, Sn powder, and Ti powder. Sn powder easily reacts with other brazing material components. By increasing the particle size of Sn powder, Sn powder easily contacts with other components. Thus, the melting point of the brazing material can be lowered. The same is true when using In instead of Sn. It is effective to increase the particle size of the component that has the effect of lowering the melting point. In addition, lowering the joining temperature can reduce the load on the joining equipment.
[0082] The powders of the constituent components of the active metal brazing filler metal are mixed to prepare a uniformly dispersed mixed powder. The mixing step of the constituent component powders is preferably performed for 10 hours or more.
[0083] Next, the mixed powder is mixed with a binder and a solvent to prepare an active metal brazing filler metal paste. In addition, the mixing step of the mixed powder, the binder, etc. is also preferably performed for 10 hours or more.
[0084] An active metal brazing paste is applied to at least one of a ceramic substrate or a copper plate. The thickness of the active metal brazing paste layer is preferably 5 μm to 80 μm. The thickness of the active metal brazing paste layer refers to the thickness after the applied paste is dried. When the thickness is less than 5 μm, the bonding strength may be reduced. In addition, when the thickness exceeds 80 μm, there is a possibility that the thermal stress in the bonding process will increase and the warping of the bonded body will increase. Therefore, the thickness of the active metal brazing paste layer is preferably 5 μm to 80 μm, and more preferably 10 μm to 50 μm.
[0085] After the step of applying the active metal brazing paste, a step of placing a member not coated with the paste on a member coated with the paste is performed. For example, in the case where the active metal brazing paste is applied to a ceramic substrate, a copper plate is placed on the ceramic substrate. The active metal brazing paste may be applied to both sides of the ceramic substrate, and copper plates may be placed on both sides. The active metal brazing paste may also be applied to a copper plate, and the ceramic substrate may be placed on the copper plate.
[0086] Next, a joining process is performed at a joining temperature of 800°C or less. The joining temperature refers to the highest temperature reached after a certain period of time. When the joining temperature is high, the grain growth of the copper grains constituting the copper plate is promoted. In the existing active metal joining method, the joining temperature is about 850°C. When the joining temperature exceeds 800°C, the grain growth of the copper plate becomes larger. When the grain growth of the copper plate is large, large grains with a long diameter exceeding 400μm are easily generated.
[0087] The bonding temperature is preferably 800°C or less, more preferably 700°C or less. In addition, the lower limit of the bonding temperature is not particularly limited, but is preferably 500°C or more. When the bonding temperature is low, there is a possibility that the reliability of the bonding is reduced. Therefore, the bonding temperature is preferably 500°C to 800°C, more preferably 550°C to 700°C. In addition, the holding time of the bonding temperature is preferably 100 minutes or less, more preferably 30 minutes or less.
[0088] In the case of bonding at a temperature exceeding 800°C, it is preferred to set the heating rate to 20°C / minute or more. By accelerating the heating rate, the amount of heat from room temperature to the bonding temperature can be reduced. Thus, an effect equivalent to a bonding temperature below 800°C can be obtained. In addition, as a bonding temperature, a temperature exceeding 800°C and below 950°C can be cited. The upper limit of the heating rate is not particularly limited, but is preferably below 100°C / minute. It is preferred to set the heating rate from room temperature to the bonding temperature to 20 to 100°C / minute, and more preferably to 30 to 70°C / minute. When the heating rate exceeds 100°C / minute, there is a possibility that control becomes difficult. In addition, the cooling rate from the bonding temperature to room temperature is also preferably within the range of 20 to 100°C / minute. By accelerating the heating rate and the cooling rate, it can be set to the same amount of heat as below 800°C.
[0089] In addition, the atmosphere in the bonding step is preferably a vacuum atmosphere or a nitrogen atmosphere.
[0090] The pressure in the vacuum is preferably 10 -3 Pa or less. In a vacuum, it is possible to suppress nitridation of Ti in the brazing material before reacting with the ceramic substrate.
[0091] A nitrogen atmosphere refers to an atmosphere containing 90 vol% to 100 vol% nitrogen. It is believed that if nitrogen is present in the atmosphere during the bonding process, Ti will be converted into titanium nitride before reacting with the ceramic substrate. When the Ti content in the brazing material is 6 mass % or more, Ti can react fully with the ceramic substrate even in a nitrogen atmosphere.
[0092] The bonding process can be in any form of a batch type or a continuous type. The batch type is a method of placing a ceramic substrate and a copper plate into a storage container and performing a heat treatment. The continuous type is a method of placing a ceramic substrate and a copper plate on a belt conveyor and performing a heat treatment while moving them. The batch type is suitable for bonding processes in a vacuum. The continuous type is suitable for bonding processes in a nitrogen atmosphere. In the case of the batch type, the holding time of the bonding temperature can be shortened. In the case of the continuous type, the holding time of the bonding temperature becomes longer, but since the heat treatment can be performed continuously, the mass productivity is improved. The batch type bonding device is also called a batch furnace, and the continuous type bonding device is also called a continuous furnace.
[0093] The Ti concentration in the bonding layer 4 can be controlled by lowering the bonding temperature and shortening the holding time at the bonding temperature.
[0094] As described above, the constituent components of the active metal brazing filler metal are uniformly mixed. Therefore, Ti is uniformly dispersed at the stage of the active metal brazing filler metal paste layer. In addition, at the stage of the active metal brazing filler metal paste layer, a layer containing titanium as a main component is not formed.
[0095] By performing the bonding process, a layer containing titanium as a main component can be formed. As in the prior art, when the bonding temperature is as high as 850° C., Ti is concentrated in the layer containing titanium as a main component. As a result, Ti is aggregated in the first region 5, and M1 / M2 becomes about 10.
[0096] By setting the joining temperature to 800°C or less, and further to 550°C to 700°C, M1 / M2 can be controlled. By lowering the joining temperature, the amount of Ti concentrated in the layer with titanium as the main component can be reduced, so that Ti remains in the second region 6. Similarly, by setting the holding time of the joining temperature to 60 minutes or less, and further to 30 minutes or less, the amount of Ti concentrated in the layer with titanium as the main component can be reduced, so that Ti remains in the second region 6. In addition, by increasing the content of Ti or TiH2 as a constituent component of the active metal brazing filler metal (for example, 5% by mass or more), the amount of Ti in the second region can also be increased. As a result, M1 / M2 can be within the range of 0.1 to 5.
[0097] Furthermore, by uniformly mixing the mixed powder of the active metal brazing filler metal, the variation of the Ti concentration in the second region 6 can be controlled to be within ±20%.
[0098] That is, in the case of a batch method performed in a vacuum, it is effective to lower the bonding temperature to 800° C. or lower, and further to 700° C. or lower.
[0099] In the case of the continuous method performed in a nitrogen atmosphere, the temperature can be higher than 800°C. By accelerating the heating rate or the cooling rate, the holding time of the bonding temperature can be shortened. As a result, the amount of Ti concentrated in the layer with titanium as the main component can be reduced, and Ti can be left in the second region 6. In addition, for the continuous method performed in a nitrogen atmosphere, an active metal brazing material that does not contain Ag is effective.
[0100] In addition, the bonded body subjected to the bonding process forms TiSi, CuSn and TiSn in the second region 6. TiSi is formed by the reaction of titanium and silicon. CuSn is formed by the reaction of copper and tin. TiSn is formed by the reaction of titanium and tin. In addition, the atomic ratio of each compound is not limited to 1:1.
[0101] When the bonding process is performed in a vacuum, the mass ratio of the compounds in the second region 6 preferably satisfies TiSi>TiSn and CuSn>TiSn. Among TiSi, CuSn, and TiSn, CuSn has the lowest melting point. The heating rate of the bonding process in a vacuum is as slow as about 1 to 2°C / minute. By increasing the amount of CuSn formed in the slow heating process, the amount of Ti in the second region 6 can be controlled.
[0102] In the bonded body, the vertical and horizontal dimensions of the ceramic substrate 2 are preferably the same as those of the copper plate 3. The thermal conductivity of the ceramic substrate 2 is preferably 60 W / m·K or more. The copper plates 3 are preferably bonded to both surfaces of the ceramic substrate 2.
[0103] The theoretical value of the thermal conductivity of copper is about 398W / m·K. By making the longitudinal and transverse dimensions of the ceramic substrate 2 the same as those of the copper plate 3, the conduction mode of heat to the active metal brazing paste layer becomes uniform. Similarly, by increasing the thermal conductivity of the ceramic substrate 2 and arranging the copper plates 3 on both sides, the conduction mode of heat can also be made uniform. As a result, the deviation of the Ti concentration in the second region 6 can be within ±20%, and further within ±10%. Even if the size of the joint 1 becomes larger, the deviation of the Ti concentration can be suppressed. Therefore, even if the size of the joint is as large as more than 200 mm in length and more than 200 mm in width, the deviation of the Ti concentration can be suppressed.
[0104] In addition, even if the longitudinal dimension or the lateral dimension of the joint body is as large as 200 mm or more, the warpage of the joint body can be made less than 0.1 mm. In addition, even if the thickness of the copper plate on the surface side is different from the thickness of the copper plate on the back side, the warpage of the joint body can be made less than 0.1 mm.
[0105] Through the above process, a joint body formed by joining a ceramic substrate and a copper plate can be manufactured. As needed, the copper plate 3 is given a circuit portion 7 or a heat sink 8 structure. By giving the circuit portion 7, the joint body 1 becomes a ceramic copper circuit substrate 10. Since the Ti concentration in the first region 5 and the second region 6 is controlled, the TCT characteristics can be improved. In addition, since the size of the joint body 1 can be increased, it is suitable for obtaining multiple joint bodies. Obtaining multiple (multi-piece) refers to a method of cutting a large joint body to obtain a small joint body. There is also a method of dividing the joint body or a method of dividing the ceramic copper circuit substrate. In order to facilitate division, scribing can be implemented.
[0106] Example
[0107] (Examples 1 to 15, Comparative Examples 1 to 3)
[0108] As ceramic substrates, silicon nitride substrates and aluminum nitride substrates shown in Table 1 were prepared.
[0109] Table 1
[0110]
[0111] Next, copper plates were prepared as shown in Table 2. All the copper plates were oxygen-free copper.
[0112] Table 2
[0113] Copper Plate Thickness(mm) Copper Plate 1 0.6 Copper Plate 2 0.8 Copper Plate 3 0.3
[0114] Next, active metal brazing materials shown in Table 3 were prepared. For active metal brazing materials 1 to 3, the particle size of Sn powder was the largest. For active metal brazing material 4, the particle size of Ag powder was the largest. The mixing time of the constituent components of brazing materials 1 to 3 and 5 to 6 was more than 10 hours. The mixing time of the constituent components of brazing material 4 was 5 hours. The melting point of the brazing material was determined by measuring the DSC curve as described above.
[0115] Table 3
[0116]
[0117] Next, the bonding process was carried out using the ceramic substrate, the copper plate, and the active metal brazing filler metal. The vertical and horizontal dimensions of the copper plate were consistent with those of the ceramic substrate. -3 Pa or less is indicated as vacuum. In addition, the case where the bonding process is performed in a nitrogen atmosphere with a nitrogen content of 98 vol% or more is indicated as nitrogen. For a bonding process with a bonding temperature of 800°C or less, the heating rate from room temperature to the bonding temperature and the cooling rate from the bonding temperature to room temperature are set within the range of 1 to 10°C / minute. In addition, for Examples 13 and 14 in which the bonding temperature exceeds 800°C, the heating rate from room temperature to the bonding temperature and the cooling rate from the bonding temperature to room temperature are set within the range of 30 to 70°C / minute. The bonding process in a vacuum is performed in a batch furnace. In addition, the bonding process in a nitrogen atmosphere is performed in a continuous furnace. The combination of each raw material is shown in Table 4.
[0118] Table 4
[0119]
[0120] The bonded bodies of the examples and comparative examples were produced by the above steps. EDX analysis was performed on an arbitrary cross section of each bonded body. Thus, the thickness of the first region, the thickness of the second region, and the Ti concentration of each region were analyzed.
[0121] For EDX analysis, 200 μm length × thickness was set as the measurement area, and regional analysis was performed. In addition, the average values of any three locations were expressed as M1 and M2. The Ti concentration was calculated in at%. When calculated in at%, the total of the components other than O (oxygen), N (nitrogen), and C (carbon) was set to 100 at%. The other conditions were as described above. The results are shown in Table 5.
[0122] Table 5
[0123]
[0124] The analysis results of Examples 1 to 15 shown in Table 5 show that in the bonded bodies of the Examples, M1 / M2 is in the range of 0.1 to 5. In addition, a layer containing titanium as a main component and having TiN in the range of 65 mass % to 100 mass % is observed in the first region.
[0125] The second region 6 of the bonded body bonded in vacuum satisfied the mass ratios of TiSi>TiSn and CuSn>TiSn. On the other hand, the bonded body bonded in nitrogen atmosphere did not necessarily satisfy the above relationship.
[0126] In addition, the warping amount of the joint bodies of the embodiments and comparative examples was measured. As the warping amount of the joint body, the warping amount of the long side was measured. The joint body with a warping amount of 0.1 mm or less on the long side was represented as a good product (○), and the joint body with a warping amount exceeding 0.1 mm was represented as a defective product (×). The joint bodies were made separately, and the worst value among the 50 joint bodies was represented. The results are shown in Table 5.
[0127] Table 6
[0128] Warpage of the joint body Example 1 ○ Example 2 ○ Example 3 ○ Example 4 ○ Example 5 ○ Example 6 ○ Example 7 ○ Example 8 ○ Example 9 ○ Example 10 ○ Embodiment 11 ○ Example 12 ○ Example 13 ○ Embodiment 14 ○ Embodiment 15 ○ Comparative Example 1 × Comparative Example 2 × Comparative Example 3 ×
[0129] According to Table 6, the warpage of the joint body of the embodiment is as small as 0.1 mm or less. Even if the thickness of the copper plate on the front side and the back side is different as in Example 7, Example 8, Example 10 and Example 12, the warpage of the joint body can be reduced. In contrast, the warpage of the joint body of the comparative example exceeds 0.1 mm.
[0130] Next, each assembly was etched to form a circuit portion and a heat sink. In addition, each assembly was divided into four to obtain a plurality of ceramic copper circuit substrates. The shapes of the circuit portion and the heat sink were the same between the embodiment and the comparative example. Twelve divided assembly were prepared.
[0131] The TCT characteristics of each ceramic copper circuit board were investigated.
[0132] For the TCT test, -40°C × 30 minutes → room temperature × 10 minutes → 170°C × 30 minutes → room temperature × 10 minutes is considered as one cycle. The bonded body using silicon nitride substrates was tested for 2000 cycles and 3000 cycles. In addition, the bonded body using aluminum nitride substrates was tested for 300 cycles and 600 cycles.
[0133] The 12 joints with no defects were set as the best quality (◎), the joints with one defect were set as good quality (○), and the joints with two or more defects were set as defective (×). The results are shown in Tables 7 and 8.
[0134] Table 7
[0135]
[0136] Table 8
[0137]
[0138] The ceramic copper circuit substrate of the embodiment has good TCT characteristics. It is known that the TCT characteristics are improved by controlling the Ti concentration of the bonding layer. In addition, even if the bonded body is enlarged, the Ti concentration can be controlled, so even if multiple bodies are obtained, the reliability is good.
[0139] In contrast, the ratio M1 / M2 of the Ti concentration in the bonding layer of the comparative example is outside the range of 0.1 to 5, so the TCT characteristics vary. This is considered to be because the variation in Ti concentration has an effect as the size of the bonded body increases. Therefore, it is not suitable for obtaining a plurality of them.
[0140] The above examples illustrate several embodiments of the present invention, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, changes, etc. can be made without departing from the scope of the main purpose of the invention. Modifications of these embodiments are included in the scope and main purpose of the invention, and are included in the invention described in the claims and their equivalents. In addition, the above-mentioned embodiments can be combined with each other and implemented.
Claims
1. A conjugate, characterized in that: It has: Silicon nitride substrate, Copper plate, and a bonding layer disposed on at least one side of the silicon nitride substrate and bonding the silicon nitride substrate to the copper plate; The bonding layer contains titanium, The bonding layer has: a first region including a layer having titanium as a main component, the layer being formed at an interface between the bonding layer and the silicon nitride substrate, and a second region located between the first region and the copper plate; When the Ti concentration in the range of 200 μm×thickness of the measurement region of each of the first region and the second region is measured by EDX, the ratio M1 / M2 of the titanium concentration M1 at % in the first region to the titanium concentration M2 at % in the second region is 0.5 to 5. The titanium concentration M2 of the second region is in the range of 0.5 at% to 15 at%, A plurality of the measurement regions are set in the second region, and when Ti concentrations in the respective measurement regions are measured by EDX, a deviation in Ti concentration between the plurality of measurement regions is within ±20%.
2. The joint body according to claim 1, characterized in that: The thickness of the first region is 5 μm or less.
3. The joint body according to claim 1 or 2, characterized in that: The thickness of the second region is greater than or equal to 5 μm and less than or equal to 70 μm.
4. The joint body according to claim 1 or 2, characterized in that: TiSi, CuSn and TiSn exist in the second region.
5. The joint body according to claim 3, characterized in that: TiSi, CuSn and TiSn exist in the second region.
6. The joint body according to claim 1 or 2, characterized in that: The copper plate has a thickness of 0.6 mm or more.
7. The joint body according to claim 5, characterized in that: The copper plate has a thickness of 0.6 mm or more.
8. The joint body according to claim 1 or 2, characterized in that: The second region contains any one or two selected from silver and copper.
9. The joint body according to claim 7, characterized in that: The second region contains any one or two selected from silver and copper.
10. The joint body according to claim 1 or 2, characterized in that: The copper plates are respectively arranged on both surfaces of the silicon nitride substrate.
11. The joint body according to claim 9, characterized in that: The copper plates are respectively arranged on both surfaces of the silicon nitride substrate.
12. A ceramic copper circuit substrate, characterized in that: It comprises the joined body according to any one of claims 1 to 11, The copper plate disposed on at least one surface of the silicon nitride substrate is provided with a circuit structure.
Citation Information
Patent Citations
Bonding body, circuit board and semiconductor device
WO2018021472A1